2013
DOI: 10.1159/000357329
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Volumetry of the Cerebrospinal Fluid Space in Idiopathic Normal Pressure Hydrocephalus

Abstract: Objectives: To measure the cerebrospinal fluid (CSF) space volume in idiopathic normal pressure hydrocephalus (INPH), we developed a software that allows us to automatically measure the regional CSF space and compared the volumes of the ventricle systems (VS), Sylvian fissures (SF) and sulci at high convexity and midline (SHM) among INPH patients, Alzheimer's disease (AD) patients and healthy volunteers (HVs). Methods: Fifteen INPH patients, 15 AD patients and 15 HVs were retrospectively selected for this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(34 citation statements)
references
References 37 publications
0
31
0
3
Order By: Relevance
“…26 The value of DESH in differentiating iNPH from other neurologic diseases has been confirmed by several studies. [27][28][29][30] Several diagnostic criteria for iNPH have recently been proposed. 1,8 One recent study reported that the effectiveness of shunt surgery for patients who were diagnosed according to one of these guidelines remained at 62.7% in terms of the mRS. 31 The incorporation of neuroimaging features that are predictive of surgical outcomes into the diagnostic criteria would thus improve the efficacy of shunt surgery.…”
Section: Discussionmentioning
confidence: 99%
“…26 The value of DESH in differentiating iNPH from other neurologic diseases has been confirmed by several studies. [27][28][29][30] Several diagnostic criteria for iNPH have recently been proposed. 1,8 One recent study reported that the effectiveness of shunt surgery for patients who were diagnosed according to one of these guidelines remained at 62.7% in terms of the mRS. 31 The incorporation of neuroimaging features that are predictive of surgical outcomes into the diagnostic criteria would thus improve the efficacy of shunt surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches and indices for quantification of ventricular enlargement exist. Ventricular dilatation is most accurately estimated using volumetric, three dimensional approaches (Toma et al, 2011; Ishii et al, 2013; Ragan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Ishii et al (2013) described software that enables automatic measuring of the regional CSF space and comparing the volumes of ventricular systems, Sylvian fissures and sulci at high convexity in NPH patients, Alzheimer's patients, and healthy volunteers. The analysis was based on 1.5 and 3 tesla MRI.…”
Section: Discussionmentioning
confidence: 99%